Apakah Kegel Exercise Berpengaruh terhadap Pengeluaran Urine Ibu Post Partum Pervaginam? - Erniwati, Erniwati; PH, Livana (Jurnal Kebidanan Malakbi, 2020)
The childbirth II causes an excessive emphasis on the pelvic floor muscles, so that the weakness of the pelvic floor muscles occurs and results in a disruption in the urging system. With Kegel exercise techniques that have a function to tighten the pubococcygeus muscles, as a bladder supporter, will reduce the disruption in the system of urging. This study aims to determine the benefits of Kegel exercise on vaginal post partum urine output. Quantitative research with interventional/experimental, urine output dependent variable and Kegel exercise independent variable. After doing research at BPM Farida Gumilir Cilacap the period of December. The results of the study showed that no exercise kegel benefit to the production of urine post a delivery in BPM Farida Gumilir Cilacap. BPM and Puskesmas can make the results of this research as input materials in providing care for the mother of Nifas, to further improve the quality of service and approach to patients maternity, NIFAS and society in general to support the restoration of the condition of the mother Nifas.